Negative plate, preparation method thereof and secondary battery
By using porphyrin-based compounds to graft silicon particles in the coating layer of the negative electrode sheet, the problem of degradation of lithium battery cycle performance is solved, and higher battery stability and capacity retention are achieved.
Patent Information
- Application Number
- CN202411495006.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-24
AI Technical Summary
During the charging and discharging cycle of lithium batteries, due to the deintercalation of lithium ions, the transition metal ions in the positive electrode active material dissolve and migrate to the negative electrode, destroying the SEI film on the negative electrode surface and reducing the cycling performance of the battery.
The grafted silicon particles of porphyrin compound into the coating layer of the negative electrode sheet are introduced to efficiently adsorb transition metal ions, preventing them from depositing on the negative electrode surface, enhancing the cycling performance of the battery, and preventing the secondary from being used through the design of the cladding and functional layer Reaction and capacity loss.
It effectively improves the cycling performance and first discharge capacity of the battery, improves the initial discharge capacity of the negative electrode sheet, and significantly improves the stability and capacity retention rate of the battery.
Smart Images

Figure CN119275228A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery preparation, and in particular to a negative electrode sheet and a preparation method thereof, and a secondary battery. Background Art
[0002] During the charge and discharge cycle of lithium batteries, the continuous deintercalation of lithium ions causes structural distortion. The transition metal ions in the positive electrode active material will inevitably dissolve into the electrolyte and migrate to the negative electrode through the diaphragm, destroying the solid electrolyte interface (SEI) film on the negative electrode surface, thereby increasing the negative electrode interface resistance and reducing the battery's cycle performance.
[0003] In existing research, the method to solve the above technical problems is usually to add a metal chelating agent to the positive electrode or the separator to adsorb the transition metal ions dissolved from the positive electrode active material. Currently, there is no research on improving the negative electrode structure to solve the above problems. Summary of the invention
[0004] To solve the above problems, the purpose of the embodiments of the present application includes providing a negative electrode sheet and a preparation method thereof and a secondary battery, which can improve the first discharge gram capacity of the negative electrode sheet while efficiently adsorbing transition metal ions, thereby effectively improving the cycle performance of the battery.
[0005] In a first aspect, an embodiment of the present application provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode coating layer disposed on the surface of the negative electrode current collector, wherein the negative electrode coating layer comprises a negative electrode active material and porphyrin compound grafted silicon particles.
[0006] In the above technical solution, by introducing porphyrin compound grafted silicon particles into the negative electrode coating layer, the electrolyte has good wettability, and can efficiently adsorb transition metal ions dissolved from the positive electrode active material, prevent transition metal ions from being deposited on the negative electrode surface to destroy the SEI film, and enhance the battery's cycle performance. In addition, the porphyrin compound grafted silicon particles can partially participate in the battery's electrochemical reaction as an active substance, thereby increasing the initial discharge gram capacity of the negative electrode sheet.
[0007] In some embodiments of the present application, a coating layer is provided on the surface of the negative electrode active material, and the coating layer includes porphyrin compound grafted silicon particles.
[0008] Optionally, the coating layer has a thickness of 0.1 nm to 1 μm.
[0009] In the above technical scheme, by forming a coating layer on the surface of the negative electrode active material, while efficiently adsorbing transition metal ions, the negative electrode active material can be prevented from directly contacting the electrolyte, thereby inhibiting the occurrence of side reactions, and reducing the capacity loss caused by the volume expansion of the electrode material, further improving the cycle performance of the battery.
[0010] In some embodiments of the present application, the negative electrode coating layer includes a negative electrode active layer covering the negative electrode current collector, and a functional layer covering the negative electrode active layer, the negative electrode active layer includes a negative electrode active material, and the functional layer includes porphyrin compound grafted silicon particles.
[0011] Optionally, the thickness of the functional layer is 1 nm to 10 μm.
[0012] In the above technical solution, the porous structure of the functional layer is conducive to enhancing the wettability of the electrode material and the electrolyte, shortening the transmission path of lithium ions, and providing sufficient space for the mechanical strain of the negative electrode active material, thereby further improving the cycle performance of the battery.
[0013] In some embodiments of the present application, the functional layer further includes inorganic oxides and / or polymers.
[0014] Optionally, the inorganic oxide includes at least one of boehmite, alumina, silica, titania, ferric oxide or ferrous oxide.
[0015] Optionally, the polymer includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan.
[0016] In the above technical solution, adding inorganic oxides and / or polymers to the functional layer can greatly improve the mechanical strength and processing performance of the functional layer, while reducing the production cost.
[0017] In a second aspect, an embodiment of the present application provides a method for preparing the above-mentioned negative electrode sheet, comprising the following steps:
[0018] A negative electrode current collector is provided, and a negative electrode coating layer is formed on the surface of the negative electrode current collector to obtain a negative electrode sheet. The negative electrode coating layer includes a negative electrode active material and porphyrin compound grafted silicon particles.
[0019] In some embodiments of the present application, a method for forming a negative electrode coating layer on the surface of a negative electrode current collector includes:
[0020] Coating the surface of the negative electrode active material with porphyrin compound-grafted silicon particles to form a coating layer;
[0021] The negative electrode active material with the coating layer is mixed with a binder and a conductive agent to obtain a coating slurry, and the coating slurry is coated on the surface of the negative electrode current collector to form a negative electrode coating layer.
[0022] Optionally, the coating layer is formed by a method including liquid phase coating, ball milling or spraying.
[0023] In some embodiments of the present application, the negative electrode coating layer includes a stacked negative electrode active layer and a functional layer, and the method for forming the negative electrode coating layer on the surface of the negative electrode current collector includes:
[0024] Providing an active slurry, the active slurry comprising a mixed negative electrode active material, a binder and a conductive agent, and coating the active slurry on the surface of the negative electrode current collector to form a negative electrode active layer;
[0025] A functional slurry is provided, the functional slurry includes porphyrin compound grafted silicon particles, and the functional slurry is coated on the surface of the negative electrode active layer to form a functional layer.
[0026] Optionally, the functional layer is formed by roller coating or spray coating.
[0027] In some embodiments of the present application, the method for preparing porphyrin compound grafted silicon particles comprises the following steps:
[0028] The porphyrin compound having an alkenyl group is dissolved in a solvent and mixed with mercapto-functionalized silicon particles, and a grafting reaction is performed under ultraviolet light to prepare the porphyrin compound grafted silicon particles.
[0029] In the above technical scheme, porphyrin compounds with alkenyl groups and mercapto-functionalized silicon particles are selected as raw materials. The alkenyl groups and mercapto groups can directly react under ultraviolet light to complete the grafting. The preparation method is simple, the grafting rate is high, and there are few by-products. The prepared porphyrin compound grafted silicon particles are not easy to undergo chemical reactions in the battery system, the chemical bonds are not easy to break, and have excellent stability.
[0030] In some embodiments of the present application, the mercapto functionalized silicon particles are 3-mercaptopropyl grafted silicon particles. The porphyrin compound having an alkenyl group includes at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt.
[0031] In the above technical solution, specific mercapto-functionalized silicon particles and porphyrin compounds are selected, and the raw materials are simple and easy to obtain, which can improve the reaction efficiency and reduce the production cost.
[0032] In some embodiments of the present application, the grafting reaction temperature is 40 to 80° C., and the time is 6 to 24 hours.
[0033] Optionally, the solvent is methanol;
[0034] Optionally, after the grafting reaction, the method further comprises: filtering and washing with methanol, and vacuum drying at 60-100°C.
[0035] In the above technical solution, by controlling the conditions of the grafting reaction, the grafting stability and grafting rate can be enhanced and the purity of the product can be ensured.
[0036] In a third aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, the above-mentioned negative electrode sheet, a separator and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator.
[0037] Since the negative electrode coating layer is introduced into the negative electrode sheet, the cycle performance of the secondary battery can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode sheet provided in an embodiment of the present application;
[0040] Figure 2 A schematic diagram of the cross-sectional structure of another negative electrode sheet provided in an embodiment of the present application.
[0041] Description of reference numerals:
[0042] 100 - negative electrode sheet; 10 - negative electrode current collector; 20 - negative electrode coating layer; 202 - negative electrode active material; 204 - coating layer; 22 - negative electrode active layer; 24 - functional layer. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0044] During the charge and discharge process of lithium-ion batteries, the continuous deintercalation of lithium ions causes structural distortion, and the transition metal ions in the positive electrode active material will slowly dissolve into the electrolyte and migrate to the negative electrode, destroying the SEI film on the surface of the negative electrode, resulting in a decrease in the cycle performance of the battery. Although the prior art discloses the addition of metal complexing agents such as porphyrin and porphine to the positive electrode or the diaphragm to inhibit the dissolution of transition metal ions, the researchers of this application have found that in a long cycle system, these metal complexing agents will reduce the cycle performance of the battery. This may be because these substances will slowly electrochemically oxidize on the positive electrode side, affecting the CEI on the positive electrode surface, and then affecting the cycle stability of the battery. Because such substances will swell, the migration ability of lithium ions between the electrolyte and the positive electrode active material, between the diaphragm and the positive electrode sheet will be reduced, or the ion permeability of the diaphragm will be reduced, thereby reducing the electrochemical performance of the battery. In addition, the wettability between this type of small molecule organic matter and the electrolyte is poor. Only the outermost layer of the porphyrin compounds in the form of particles can effectively adsorb transition metal ions. The material utilization rate is very low and the adsorption effect is poor.
[0045] Based on this, the researchers of this application have found through creative research that the porphyrin compound-grafted silicon particles obtained by grafting functionalized silicon particles with porphyrin compounds, when added to the negative electrode coating layer, can efficiently adsorb transition metal ions and improve the cycle performance of the battery. In addition, the porphyrin compound-grafted silicon particles can partially participate in the electrochemical reaction of the battery as an active substance, thereby improving the initial discharge capacity of the negative electrode sheet.
[0046] A negative electrode sheet and a preparation method thereof and a secondary battery according to an embodiment of the present application are described in detail below.
[0047] First, an embodiment of the present application provides a negative electrode sheet and a preparation method thereof. The negative electrode sheet includes a negative electrode current collector and a negative electrode coating layer disposed on the surface of the negative electrode current collector. The negative electrode coating layer includes a negative electrode active material and porphyrin compound grafted silicon particles.
[0048] The preparation method of the negative electrode sheet may include the following steps: providing a negative electrode current collector, forming a negative electrode coating layer on the surface of the negative electrode current collector, and obtaining a negative electrode sheet, wherein the negative electrode coating layer includes a negative electrode active material and porphyrin compound grafted silicon particles.
[0049] It should be noted that the types of negative electrode active materials and negative electrode current collectors are not limited in this application and can be selected according to actual application needs. As an example, the negative electrode active material may include at least one of graphite, hard carbon, soft carbon, graphene, silicon carbon or silicon oxygen. Optionally, the particle size of the negative electrode active material is 10nm to 100μm.
[0050] The thickness of the negative electrode sheet may be 1 μm to 1 mm.
[0051] The preparation method of porphyrin compound grafted silicon particles comprises the following steps: dissolving a porphyrin compound having an alkenyl group in a solvent and mixing the mixture with mercapto functionalized silicon particles, and performing a grafting reaction under ultraviolet light to prepare porphyrin compound grafted silicon particles.
[0052] The porphyrin compound having an alkenyl group may be protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt, protoporphyrin dilithium salt. The mercapto functionalized silicon particles may be 3-mercaptopropyl grafted silicon particles.
[0053] The diameter of the thiol-functionalized silicon particles may be 0.1 nm to 1 μm, and the thiol loading may be 0.1 mmol / g to 10 mmol / g. As an example, the diameter of the thiol-functionalized silicon particles may be 100 nm, and the thiol loading may be 0.3 mmol / g.
[0054] By controlling the diameter of the thiol functionalized silicon particles, the diameter of the porphyrin compound grafted silicon particles can be adjusted to 0.1nm to 1μm, so that the surface of the negative electrode active material can be effectively coated. In addition, by correspondingly controlling the thiol loading, it can be fully reacted with the olefin group in the porphyrin compound.
[0055] In the grafting reaction, the molar ratio of the alkenyl group in the porphyrin compound having an alkenyl group and the mercapto group in the mercapto-functionalized silicon particles can be controlled to be about (1-20): 1. It should be noted that in practical applications, the excess of alkenyl groups can be controlled, for example, the molar ratio of alkenyl groups to mercapto groups can be controlled to be 12:1, so that the mercapto grafting rate after the reaction reaches 100%.
[0056] The conditions of the grafting reaction include: the grafting reaction temperature is 40-80°C, the time is 6-24 hours. The solvent can be methanol, preferably anhydrous methanol. After the grafting reaction, the following steps are further performed: filtering and washing with methanol, and vacuum drying at 60-100°C.
[0057] As an example, the general structural formula of porphyrin compound grafted silicon particles is shown in formula (I):
[0058]
[0059] Among them, R 3 , R 5 , R 7 , R 8 , R 10 , R 12 , R 13 , R 15 , R 17 , R 18 , R 20 are each independently phenyl, vinyl, allyl, Cn H 2n+1 , C n H 2n OH, C n H 2n CHO, C n H 2n COOH, C n H 2n COONa、C n H 2n COOLi, C n H 2n COOC n H 2n , C n H 2n SH, n is an integer between 0 and 20; i and j are each independently an integer between 0 and 10.
[0060] As an example, the grafting reaction process of protoporphyrin and 3-mercaptopropyl grafted silicon particles is shown in the following formula:
[0061]
[0062] As an example, Figure 1 For a schematic diagram of the cross-sectional structure of a negative electrode sheet provided in an embodiment of the present application, see Figure 1 The negative electrode sheet 100 includes a negative electrode current collector 10 and a negative electrode coating layer 20 disposed on both sides of the negative electrode current collector 10. The negative electrode coating layer 20 includes a negative electrode active material 202. A coating layer 204 is disposed on the surface of the negative electrode active material 202. The coating layer 204 includes porphyrin compound grafted silicon particles.
[0063] At this time, the method of forming the negative electrode coating layer on the surface of the negative electrode current collector may include:
[0064] Coating the surface of the negative electrode active material with porphyrin compound-grafted silicon particles to form a coating layer;
[0065] The negative electrode active material with the coating layer is mixed with a binder and a conductive agent to obtain a coating slurry, and the coating slurry is coated on the surface of the negative electrode current collector to form a negative electrode coating layer.
[0066] The coating layer can be formed by liquid phase coating, ball milling or spraying. For example, the surface of the negative electrode active material and the porphyrin compound grafted silicon particles are ball milled at high speed on a high energy ball mill.
[0067] The thickness of the coating layer may be 0.1 nm to 1 μm, including but not limited to 1 nm, 10 nm, 1 μm, etc.
[0068] As another example, Figure 2This is a schematic diagram of the cross-sectional structure of another negative electrode sheet provided in the embodiment of the present application. Figure 2 The negative electrode sheet 100 includes a negative electrode current collector 10 and a negative electrode coating layer 20 disposed on both sides of the negative electrode current collector 10. The negative electrode coating layer 20 includes a negative electrode active layer 22 covering the negative electrode current collector 10, and a functional layer 24 covering the negative electrode active layer 22. The negative electrode active layer 22 includes a negative electrode active material 202, and the functional layer 24 includes porphyrin compound grafted silicon particles.
[0069] At this time, the method of forming the negative electrode coating layer on the surface of the negative electrode current collector may include:
[0070] Providing an active slurry, the active slurry comprising a mixed negative electrode active material, a binder and a conductive agent, and coating the active slurry on the surface of the negative electrode current collector to form a negative electrode active layer;
[0071] A functional slurry is provided, the functional slurry includes porphyrin compound grafted silicon particles, and the functional slurry is coated on the surface of the negative electrode active layer to form a functional layer.
[0072] The raw materials of the functional layer may also include inorganic oxides and / or polymers. Among them, the inorganic oxide may be selected from at least one of boehmite, alumina, silicon dioxide, titanium dioxide, ferric oxide or ferric oxide. The polymer may be selected from at least one of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan. The weight average molecular weight of the polymer may be 1,000 to 3,000,000.
[0073] The mass ratio of the porphyrin compound grafted silicon particles, the inorganic oxide and the polymer can be (1-99):(0-99):(0-99).
[0074] As an example, the thickness of the functional layer may be 1 nm to 10 μm, for example but not limited to, any one of 1 nm, 1 μm, and 10 μm, or a range between any two of the thicknesses.
[0075] The functional layer can be formed on the surface of the negative electrode active layer by roller coating, spray coating, etc. As an example, the porphyrin compound grafted silicon particles and polymer can be mixed to form a slurry, and then the slurry is ultrasonically sprayed on the surface of the negative electrode active layer and dried to form the functional layer.
[0076] In addition, an embodiment of the present application provides a secondary battery, including a positive electrode sheet, a separator, an electrolyte and the above-mentioned negative electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator.
[0077] It should be noted that the positive electrode sheet, the separator and the electrolyte can be selected from conventional ones in the art, and are not limited in this application and can be selected according to needs.
[0078] As an example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material located on the surface of the positive electrode current collector. The positive electrode active material may be LiMNO 4 or LiNO 2 , wherein M may be at least one of Fe, Co, Ni, and Mn, and N may be at least one of Ni, Co, Mn, and Al. As an example, the positive electrode active material may be lithium iron phosphate (LFN for short), lithium iron manganese phosphate (LMFN for short), lithium manganese oxide (LMO for short), lithium cobalt oxide (LCO for short), lithium nickel manganese oxide (LNMO for short), lithium nickel cobalt manganese oxide (NCM for short), and lithium nickel cobalt aluminum oxide (NCA for short).
[0079] It should be noted that the embodiments of the present application only list some positive electrode active materials used in lithium-ion batteries, but the type of battery is not limited. In actual application, sodium-ion batteries and the like can also be used.
[0080] The features and performance of the present application are further described in detail below in conjunction with embodiments and comparative examples.
[0081] Example 1-1
[0082] The present application embodiment provides a battery NC1, and the preparation method thereof comprises the following steps:
[0083] (1) Preparation of 3-mercaptopropyl grafted silicon particles
[0084] Take 100g silicon particles (particle diameter is 100nm) and slowly add them to 1L of Piranha solution under magnetic stirring, then stir at 90℃ for 1h. After completion, filter and wash with a large amount of pure water and vacuum dry the silicon particles at 60℃. Then take the above activated silicon particles, then add 600mL of toluene solution of 3-mercaptopropyltrimethoxysilane with a concentration of 60mmol / L, and stir the reaction for 12h. Finally, filter and wash the above silicon particles with acetone and pure water, and vacuum dry at 120℃ for use, to obtain 3-mercaptopropyl grafted silicon particles with a mercapto loading of 0.3mmol / g.
[0085] (2) Preparation of negative electrode active materials
[0086] Take 134.9g of protoporphyrin IX (Aladdin, CAS: 553-12-8) and dissolve it in 1214.1g of anhydrous methanol, then add 100g of 3-mercaptopropyl grafted silicon particles prepared in step (1), stir and disperse at 60°C and irradiate with ultraviolet light for 12h, then filter and wash with 12000g of anhydrous methanol, and then vacuum dry at 80°C to obtain protoporphyrin IX grafted silicon particles (hereinafter referred to as Pr-Si).
[0087] The protoporphyrin IX grafted silicon particles and graphite (Gr for short, particle diameter 13 μm) were milled at a high speed for 24 hours in a high energy ball mill at a weight ratio of 1:99 to form a coating layer on the graphite surface with a thickness of 0.3 μm.
[0088] (3) Preparation of negative electrode sheet
[0089] Take 95.6g of the above negative electrode active material, 1.5g of carboxymethyl cellulose, 1.1g of conductive carbon, and 4.5g of styrene-butadiene rubber latex (solid content 40wt%), disperse them at high speed for 8h, then coat them on both sides of a copper foil with a thickness of 8μm, then dry them at 100℃, and cut them into negative electrode sheets for use.
[0090] (4) Preparation of positive electrode
[0091] Take 96g of lithium nickel manganese oxide (LNMO, chemical formula LiNi 0.5 Mn 1.5 O 4 ), 1.8g polyvinylidene fluoride, and 2.2g conductive carbon were dispersed at high speed for 8 hours and then coated on both sides of an aluminum foil with a thickness of 12μm, then dried at 100℃ and cut into positive electrode sheets for use.
[0092] (5) Preparation of batteries
[0093] The negative electrode sheet, the positive electrode sheet and the polyethylene separator with a thickness of 14 μm are taken to form a small soft-pack battery through a lamination process, and then the battery NC1 is obtained by normal liquid injection, formation and capacity separation.
[0094] Example 1-2
[0095] The present embodiment provides a battery NC2, the preparation method of which is different from that of the embodiment 1-1 only in that:
[0096] In step (2), graphite is replaced by silicon carbon (abbreviated as SiC, particle diameter 9 μm).
[0097] Examples 1-3
[0098] The present embodiment provides a battery NC2, the preparation method of which is different from that of the embodiment 1-1 only in that:
[0099] In step (2), graphite is replaced by silicon oxide (abbreviated as SiO, particle diameter 5 μm).
[0100] Examples 1-4
[0101] The present application embodiment provides a battery NC4, the preparation method of which is different from that of embodiment 1-1 in that: in step (4), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0102] Examples 1-5
[0103] The present application embodiment provides a battery NC5, the preparation method of which is different from that of embodiment 1-2 in that: in step (4), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0104] Examples 1-6
[0105] The present application embodiment provides a battery NC6, the preparation method of which is different from that of embodiments 1-3 in that: in step (4), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (abbreviated as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0106] Examples 1-7
[0107] The present application embodiment provides a battery NC6, the preparation method of which is different from that of embodiment 1-1 in that: in step (4), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0108] Examples 1-8
[0109] The present application embodiment provides a battery NC6, the preparation method of which is different from that of embodiment 1-2 in that: in step (4), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0110] Examples 1-9
[0111] The present application embodiment provides a battery NC6, the preparation method of which is different from that of embodiments 1-3 in that: in step (4), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0112] Comparative Example 1-1
[0113] The comparative example of the present application provides a battery RC1, the preparation method of which is different from that of Example 1-1 only in that: in step (2), the negative electrode active material is graphite without any treatment, that is, no coating layer is provided on the surface.
[0114] Comparative Example 1-2
[0115] The comparative example of the present application provides a battery RC2, the preparation method of which is different from that of Examples 1-2 only in that: in step (2), the negative electrode active material is silicon carbon without any treatment, that is, no coating layer is provided on the surface.
[0116] Comparative Examples 1-3
[0117] The comparative example of the present application provides a battery RC3, the preparation method of which is different from that of Examples 1-3 only in that: in step (2), the negative electrode active material is silicon oxide without any treatment, that is, no coating layer is provided on the surface.
[0118] Comparative Examples 1-4
[0119] The comparative example of the present application provides a battery RC4, the preparation method of which is different from that of Examples 1-4 only in that: in step (2), the negative electrode active material is graphite without any treatment, that is, no coating layer is provided on the surface.
[0120] Comparative Examples 1-5
[0121] The comparative example of the present application provides a battery RC5, the preparation method of which is different from that of Examples 1-5 only in that: in step (2), the negative electrode active material is silicon carbon without any treatment, that is, no coating layer is provided on the surface.
[0122] Comparative Examples 1-6
[0123] The comparative example of the present application provides a battery RC6, the preparation method of which is different from that of Examples 1-6 only in that: in step (2), the negative electrode active material is silicon oxide without any treatment, that is, no coating layer is provided on the surface.
[0124] Comparative Examples 1-7
[0125] The comparative example of the present application provides a battery RC7, the preparation method of which is different from that of Examples 1-7 only in that: in step (2), the negative electrode active material is graphite without any treatment, that is, no coating layer is provided on the surface.
[0126] Comparative Examples 1-8
[0127] The comparative example of the present application provides a battery RC8, the preparation method of which is different from that of Examples 1-8 only in that: in step (2), the negative electrode active material is silicon carbon without any treatment, that is, no coating layer is provided on the surface.
[0128] Comparative Examples 1-9
[0129] The comparative example of the present application provides a battery RC9, the preparation method of which is different from that of Examples 1-9 only in that: in step (2), the negative electrode active material is silicon oxide without any treatment, that is, no coating layer is provided on the surface.
[0130] Comparative Examples 1-10
[0131] The comparative example of the present application provides a battery RC10, the preparation method of which is different from that of Example 1-1 only in that: in step (2), protoporphyrin IX is used instead of protoporphyrin IX grafted silicon particles to form a protoporphyrin IX coating layer on the graphite surface.
[0132] Some key preparation conditions of the batteries in the above examples and comparative examples are shown in Table 1.
[0133] Table 1 Partial preparation conditions of batteries in Examples and Comparative Examples
[0134]
[0135]
[0136] Test Example 1
[0137] The negative electrode sheets and batteries prepared in the above examples and comparative examples were subjected to negative electrode sheet gram capacity button cell test, cycle performance test and transition metal ion content test. The specific test methods are as follows:
[0138] 1. Negative electrode gram capacity button cell test
[0139] The negative electrode sheets in the examples and comparative examples were cut into small discs with a diameter of 14 mm, and then the small discs were weighed and made into CR2032 button batteries with commercial lithium sheets. Then, the button battery test process was followed to perform the test, and the first discharge gram capacity test results are shown in Table 2.
[0140] Button battery testing steps:
[0141] (1) Leave the prepared CR2032 button cell at room temperature for 24 hours;
[0142] (2) Discharge from open circuit voltage to 0.005 V at a constant current of 0.1 C, then discharge to 0.005 V at a current of 0.05 mA, and finally discharge to 0.005 V at a current of 0.01 mA;
[0143] (3) Leave for 10 minutes;
[0144] (4) Charge to 2V at a constant current of 0.1C;
[0145] (5) Set aside for 10 minutes.
[0146] 2. Battery cycle performance test
[0147] The batteries of the embodiment and the comparative example were subjected to cycle performance tests according to the following steps:
[0148] (1) Leave for 1 minute;
[0149] (2) Discharge from the open circuit voltage to the lower limit voltage at a constant current of 1C;
[0150] (3) Leave for 1 min;
[0151] (4) Charge at a constant current of 1C to the upper voltage limit, and then charge at a constant voltage of 0.05C;
[0152] (5) Leave for 1 min;
[0153] (6) Discharge at a constant current of 1C to the lower limit voltage;
[0154] (7) Leave for 1 min;
[0155] (8) Repeat steps (4) to (7) for 1000 times.
[0156] Among them, the voltage upper limit of Examples 1-1 to 1-3, Comparative Examples 1-1 to 1-3, and Comparative Example 1-10 is 4.8V, and the voltage lower limit is 3.5V; the voltage upper limit of Examples 1-4 to 1-6 and Comparative Examples 1-4 to 1-6 is 4.3V, and the voltage lower limit is 2.8V; the voltage upper limit of Examples 1-7 to 1-9 and Comparative Examples 1-7 to 1-9 is 3.85V, and the voltage lower limit is 2.5V. The cycle performance test results are shown in Table 2.
[0157] 3. Transition metal ion content test
[0158] The small soft-pack battery after 1000 cycles at room temperature was disassembled, and 0.5 g of free electrolyte was extracted, and then diluted to 10 g with dimethyl carbonate. The diluted sample was taken and the contents of Fe, Co, Ni, and Mn in the sample were determined by ICP external standard method. The measurement results are shown in Table 3.
[0159] Table 2 Performance test results of embodiments and comparative examples
[0160]
[0161]
[0162] Table 3 Summary of the content of transition metal ions in the embodiments and comparative examples
[0163]
[0164]
[0165] From the test results of Table 2 and Table 3, it can be seen that after the batteries of Examples 1-1 to 1-9 are cycled 1000 times at room temperature at 1C, the content of transition metal ions in the electrolyte is relatively low, and the minimum can reach 3ppm. Correspondingly, the negative electrode sheets of Examples 1-1 to 1-9 have a higher first discharge gram capacity, and the corresponding batteries have excellent cycle performance. After 1000 cycles at room temperature at 1C, the capacity retention rate can reach up to 95%.
[0166] By comparing the performance test results of Examples 1-1 to 1-3 and Comparative Examples 1-1 to 1-3, Examples 1-4 to 1-6 and Comparative Examples 1-4 to 1-6, and Examples 1-7 to 1-9 and Comparative Examples 1-7 to 1-9, it can be seen that in the present application, by arranging a porphyrin compound grafted silicon particle coating layer on the surface of the negative electrode active material, the transition metal ions can be efficiently adsorbed, while the initial discharge gram capacity of the negative electrode sheet is increased, and the cycle performance of the battery is improved. By comparing the performance test results of Example 1-1 and Comparative Example 1-10, it can be seen that although the pure porphyrin coating layer can also adsorb a certain amount of transition metal ions, the stability is poor during the long-term cycle process, and the cycle performance is significantly worse than that of Example 1-1.
[0167] The above-mentioned embodiments 1-1 to 1-3 and comparative examples 1-1 to 1-3 and comparative example 1-4 are batteries of a nickel manganese oxide system, the above-mentioned embodiments 1-4 to 1-6 and comparative examples 1-4 to 1-6 are batteries of a nickel cobalt manganese oxide system, and the above-mentioned embodiments 1-7 to 1-9 and comparative examples 1-7 to 1-9 are batteries of a lithium iron phosphate system. It can be seen from the contents of Tables 2 and 3 that for batteries of different positive electrode active material systems, the technical solution provided in the present application can efficiently adsorb transition metal ions dissolved from the positive electrode active material during the cycle by forming a coating layer including porphyrin compound grafted silicon particles on the surface of the negative electrode active material, and effectively improve the cycle performance during a long cycle, especially effectively improve the cycle stability of the nickel manganese oxide lithium battery system.
[0168] Example 2-1
[0169] The present application embodiment provides a battery NB1, and the preparation method thereof comprises the following steps:
[0170] (1) Preparation of porphyrin-grafted silicon particles
[0171] Take 100g silicon particles (particle diameter is 100nm) and slowly add them to 1L of Piranha solution under magnetic stirring, then stir at 90℃ for 1h. After completion, filter and wash with a large amount of pure water and vacuum dry the silicon particles at 60℃. Then take the above activated silicon particles, then add 600mL of toluene solution of 3-mercaptopropyltrimethoxysilane with a concentration of 60mmol / L, and stir the reaction for 12h. Finally, filter and wash the above silicon particles with acetone and pure water, vacuum dry at 120℃ for use, and obtain 3-mercaptopropyl grafted silicon particles. Among them, the thiol loading is 0.3mmol / g.
[0172] Take 134.9g of protoporphyrin IX (Aladdin, CAS: 553-12-8) and dissolve it in 1214.1g of anhydrous methanol, then add 100g of 3-mercaptopropyl grafted silicon particles, stir at 60°C and irradiate with ultraviolet light for 12h, then filter and wash with 12000g of anhydrous methanol, and then vacuum dry at 80°C to obtain protoporphyrin IX grafted silicon particles (abbreviated as Pr-Si).
[0173] (2) Preparation of negative electrode sheet
[0174] Take 95.6g of graphite (Gr for short, particle diameter 13μm), 1.5g of carboxymethyl cellulose (CMC for short), 1.1g of conductive carbon, and 4.5g of styrene-butadiene rubber latex (SBR for short, solid content 40wt%), and then coat them on both sides of 8μm copper foil after high-speed dispersion for 8h, and then dry them at 100℃ to form negative electrode active layers on both sides of the copper foil.
[0175] 90g protoporphyrin IX grafted silicon particles, 5g carboxymethyl cellulose, 12.5g styrene-butadiene rubber latex (solid content 40wt%) were taken and dispersed at high speed for 5h to obtain slurry. The slurry was then ultrasonically sprayed on the surface of the negative electrode active layer to form a functional layer with a thickness of 1μm, and then cut into negative electrode sheets and dried at 100℃ for use.
[0176] (3) Preparation of positive electrode
[0177] Take 96g of lithium nickel manganese oxide (LNMO, chemical formula LiNi 0.5 Mn 1.5 O 4 ), 1.8g polyvinylidene fluoride, and 2.2g conductive carbon were dispersed at high speed for 8 hours and then coated on both sides of a 12μm aluminum foil, then dried at 100°C and cut into positive electrode sheets for later use.
[0178] (4) Preparation of batteries
[0179] The negative electrode sheet, the positive electrode sheet and the polyethylene separator with a thickness of 14 μm are taken to form a small soft-pack battery through a lamination process, and then the battery NB1 is obtained by normal liquid injection, formation and capacity separation.
[0180] Example 2-2
[0181] The present embodiment provides a battery NB2, the preparation method of which is different from that of the embodiment 2-1 only in that: in step (2), the functional layer further includes aluminum oxide:
[0182] Take 95.6g of graphite (Gr for short, particle diameter 13μm), 1.5g of carboxymethyl cellulose (CMC for short), 1.1g of conductive carbon, and 4.5g of styrene-butadiene rubber latex (SBR for short, solid content 40wt%), and then coat them on both sides of 8μm copper foil after high-speed dispersion for 8h, and then dry them at 100℃ to form a negative electrode active layer on both sides of the copper foil.
[0183] 85g protoporphyrin grafted silicon particles, 5g alumina, 5g carboxymethyl cellulose, 12.5g styrene-butadiene rubber latex (solid content 40wt%) were taken and dispersed at high speed for 5h to obtain slurry. The slurry was then ultrasonically sprayed on the surface of the negative electrode active layer to form a functional layer with a thickness of 1μm, and then cut into negative electrode sheets and dried at 100℃ for use.
[0184] Example 2-3
[0185] The present embodiment provides a battery NB3, the preparation method of which is different from that of embodiment 2-1 only in that in step (2), graphite (Gr for short, particle diameter 13 μm) is replaced by silicon carbon (SiC for short, particle diameter 9 μm).
[0186] Embodiment 2-4
[0187] The present embodiment provides a battery NB4, the preparation method of which differs from that of embodiment 2-2 only in that in step (2), graphite (Gr for short, particle diameter 13 μm) is replaced by silicon carbon (SiC for short, particle diameter 9 μm).
[0188] Embodiment 2-5
[0189] The present embodiment provides a battery NB5, the preparation method of which is different from that of embodiment 2-1 only in that in step (2), graphite (Gr for short, particle diameter 13 μm) is replaced with silicon oxide (SiO for short, particle diameter 5 μm).
[0190] Embodiment 2-6
[0191] The present application embodiment provides a battery NB6, the preparation method of which differs from that of embodiment 2-2 only in that in step (2), graphite (Gr for short, particle diameter 13 μm) is replaced with silicon oxide (SiO for short, particle diameter 5 μm).
[0192] Embodiment 2-7
[0193] The present application embodiment provides a battery NB7, the preparation method of which is different from that of embodiment 2-1 in that: in step (3), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0194] Embodiment 2-8
[0195] The present application embodiment provides a battery NB8, the preparation method of which is different from that of embodiment 2-2 in that: in step (3), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0196] Embodiment 2-9
[0197] The present application embodiment provides a battery NB9, the preparation method of which is different from that of Embodiments 2-3 in that: in step (3), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0198] Embodiment 2-10
[0199] The present embodiment provides a battery NB10, the preparation method of which is different from that of Embodiments 2-4 in that: in step (3), the lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0200] Example 2-11
[0201] The present application embodiment provides a battery NB11, the preparation method of which is different from that of embodiments 2-5 in that: in step (3), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0202] Example 2-12
[0203] The present embodiment provides a battery NB12, the preparation method of which is different from that of Embodiments 2-6 in that: in step (3), lithium nickel manganese oxide is replaced with lithium nickel cobalt manganese oxide (referred to as NCM811, chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ).
[0204] Example 2-13
[0205] The present embodiment provides a battery NB13, the preparation method of which is different from that of embodiment 2-1 in that: in step (3), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0206] Example 2-14
[0207] The present embodiment provides a battery NB14, the preparation method of which is different from that of embodiment 2-2 in that: in step (3), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0208] Example 2-15
[0209] The present application embodiment provides a battery NB15, the preparation method of which is different from that of Embodiments 2-3 in that: in step (3), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0210] Example 2-16
[0211] The present embodiment provides a battery NB16, the preparation method of which is different from that of embodiments 2-4 in that: in step (3), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0212] Example 2-17
[0213] The present embodiment provides a battery NB17, the preparation method of which is different from that of embodiments 2-5 in that: in step (3), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0214] Example 2-18
[0215] The present embodiment provides a battery NB18, the preparation method of which is different from that of embodiments 2-6 in that: in step (3), lithium nickel manganese oxide is replaced with lithium iron phosphate (LFP, chemical formula LiFePO 4 ).
[0216] Comparative Example 2-1
[0217] The comparative example of the present application provides a battery RB1, the preparation method of which is different from that of Example 2-1 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0218] Comparative Example 2-2
[0219] The comparative example of the present application provides a battery RB2, the preparation method of which is different from that of Examples 2-3 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0220] Comparative Examples 2-3
[0221] The comparative example of the present application provides a battery RB3, the preparation method of which is different from that of Examples 2-5 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0222] Comparative Examples 2-4
[0223] The comparative example of the present application provides a battery RB4, the preparation method of which is different from that of Examples 2-7 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0224] Comparative Examples 2-5
[0225] The comparative example of the present application provides a battery RB5, the preparation method of which is different from that of Examples 2-9 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0226] Comparative Examples 2-6
[0227] The comparative example of the present application provides a battery RB6, the preparation method of which is different from that of Examples 2-11 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0228] Comparative Examples 2-7
[0229] The comparative example of the present application provides a battery RB7, the preparation method of which is different from that of Examples 2-13 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0230] Comparative Examples 2-8
[0231] The comparative example of the present application provides a battery RB8, the preparation method of which is different from that of Examples 2-15 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0232] Comparative Examples 2-9
[0233] The comparative example of the present application provides a battery RB9, the preparation method of which is different from that of Examples 2-17 only in that in step (2), no functional layer is formed on the surface of the negative electrode active layer.
[0234] Comparative Examples 2-10
[0235] The comparative example of the present application provides a battery RB10, the preparation method of which is different from that of Example 2-1 only in that in step (2), protoporphyrin IX is used instead of protoporphyrin IX grafted silicon particles to form a functional layer.
[0236] Some key preparation conditions of the batteries in the above examples and comparative examples are shown in Table 4.
[0237] Table 4 Partial preparation conditions of batteries in Examples and Comparative Examples
[0238]
[0239]
[0240]
[0241] Test Example 2
[0242] The negative electrode sheets and batteries prepared in the above examples and comparative examples were subjected to negative electrode sheet gram capacity button cell test, battery cycle performance test and transition metal ion content test. The specific test methods were the same as those in Experimental Example 1. The performance test results are shown in Tables 5 and 6.
[0243] Table 5 Summary of cycle performance of embodiments and comparative examples
[0244]
[0245]
[0246] Table 6 Summary of transition metal ion contents in the embodiments and comparative examples
[0247]
[0248]
[0249] From the performance test results of Table 5 and Table 6, it can be seen that after the batteries of Examples 2-1 to 2-18 are cycled 1000 times at room temperature at 1C, the content of transition metal ions in the electrolyte is relatively low, and the minimum can reach 2ppm. Correspondingly, the negative electrode sheets of Examples 2-1 to 2-18 have a higher initial discharge gram capacity, and the corresponding batteries have excellent cycle performance. After 1000 cycles at room temperature at 1C, the capacity retention rate can reach up to 96%.
[0250] The above-mentioned embodiments 2-1 to 2-6, comparative examples 2-1 to 2-3, and comparative example 2-10 are batteries of nickel manganese oxide system, embodiments 2 to 7 to 2-12, comparative examples 2-4 to 2-6 are batteries of nickel cobalt manganese oxide system, and embodiments 2-13 to 2-18, comparative examples 2-7 to 2-9 are batteries of lithium iron phosphate system. It can be seen from Tables 5 and 6 that for batteries with different positive electrode active material systems, the technical solution provided by the present application can efficiently adsorb transition metal ions dissolved from the positive electrode active material during the cycle by forming a functional layer including porphyrin compound grafted silicon particles on the surface of the negative electrode active layer, and effectively improve the cycle performance of the battery during a long cycle, especially effectively improve the cycle stability of the nickel manganese oxide lithium battery system.
[0251] In addition, by comparing the performance test results of Example 2-1 and Comparative Example 2-10, it can be seen that although the pure porphyrin functional layer can also adsorb a certain amount of transition metal ions, its stability is poor during long-term circulation, and the cycle performance is significantly worse than that of Example 2-1.
[0252] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode coating layer arranged on the surface of the negative electrode current collector, wherein the negative electrode coating layer comprises a negative electrode active material and porphyrin compound grafted silicon particles.
2. The negative electrode sheet according to claim 1, characterized in that: The surface of the negative electrode active material is provided with a coating layer, and the coating layer includes porphyrin compound grafted silicon particles; Optionally, the coating layer has a thickness of 0.1 nm to 1 μm.
3. The negative electrode sheet according to claim 1, characterized in that: The negative electrode coating layer comprises a negative electrode active layer covering the negative electrode current collector, and a functional layer covering the negative electrode active layer, the negative electrode active layer comprises the negative electrode active material, and the functional layer comprises the porphyrin compound grafted silicon particles; Optionally, the thickness of the functional layer is 1 nm to 10 μm.
4. The negative electrode sheet according to claim 3, characterized in that: The functional layer further comprises an inorganic oxide and / or a polymer; Optionally, the inorganic oxide includes at least one of boehmite, alumina, silica, titanium dioxide, ferric oxide or ferrosoferric oxide; Optionally, the polymer includes at least one of polyvinylidene fluoride, poly(vinylidene fluoride hexafluoropropylene), polytetrafluoroethylene, polyhexafluoropropylene, polyacrylate, polymethacrylate, polyacrylamide, polymethacrylamide, epoxy resin, polyvinyl pyrrolidone, carboxymethyl cellulose, sodium carboxymethyl cellulose, cellulose or chitosan.
5. A method for preparing a negative electrode sheet according to any one of claims 1 to 4, characterized in that: The following steps are involved: A negative electrode current collector is provided, and a negative electrode coating layer is formed on the surface of the negative electrode current collector to obtain a negative electrode sheet; the negative electrode coating layer comprises a negative electrode active material and porphyrin compound grafted silicon particles.
6. The preparation method according to claim 5, characterized in that: The method for forming a negative electrode coating layer on the surface of the negative electrode current collector comprises: Coating the surface of the negative electrode active material with porphyrin compound-grafted silicon particles to form a coating layer; Mixing the negative electrode active material having a coating layer with a binder and a conductive agent to obtain a coating slurry, and applying the coating slurry on the surface of the negative electrode current collector to form the negative electrode coating layer; Optionally, the coating layer is formed by a method comprising liquid phase coating, ball milling or spraying.
7. The preparation method according to claim 5, characterized in that: The negative electrode coating layer includes a stacked negative electrode active layer and a functional layer. The method for forming the negative electrode coating layer on the surface of the negative electrode current collector includes: Providing an active slurry, wherein the active slurry comprises a mixed negative electrode active material, a binder and a conductive agent; applying the active slurry on the surface of the negative electrode current collector to form the negative electrode active layer; Providing a functional slurry, wherein the functional slurry includes the porphyrin compound grafted silicon particles; coating the functional slurry on the surface of the negative electrode active layer to form the functional layer; Optionally, the method for forming the functional layer includes roller coating or spray coating.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method of the porphyrin compound grafted silicon particles comprises the following steps: The porphyrin compound having an alkenyl group is dissolved in a solvent and mixed with mercapto-functionalized silicon particles, and a grafting reaction is performed under ultraviolet light to prepare the porphyrin compound grafted silicon particles.
9. The preparation method according to claim 8, characterized in that: The mercapto-functionalized silicon particles are 3-mercaptopropyl grafted silicon particles; The porphyrin compound having an alkenyl group includes at least one of protoporphyrin, protoporphyrin monomethyl ester, protoporphyrin dimethyl ester, protoporphyrin monosodium salt, protoporphyrin disodium salt, protoporphyrin monolithium salt or protoporphyrin dilithium salt; Optionally, the grafting reaction is carried out at a temperature of 40 to 80° C. and for a time of 6 to 24 hours.
10. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet as claimed in any one of claims 1 to 4, a separator and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte infiltrates the positive electrode sheet, the negative electrode sheet and the separator.
Citation Information
Patent Citations
Preparation method of selenium-sulfur doped graphene quantum dot modified metal porphyrin nano-tube photosensitive sensing material
CN109187671A
Silicon-based negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN116470036A
Compound Particle Having Liquid Electrolyte and Secondary Battery Comprising the Same
KR1020150014897A
Sewage and wastewater complex treatment system with improved advanced treatment structure
KR102477928B1
Anode, method of manufacturing it, and battery
US20080206651A1
Cited By
Integrated structure of current collector and silicon carbon material as well as preparation method and application of integrated structure
CN122291424A
Integrated structure of current collector and silicon-carbon material, and preparation method and application thereof
CN122291424B